It Takes a Village: Discovering and Isolating the Nitrifiers - Sedlacek, Christopher J. (Frontiers in Microbiology, 2020)
It has been almost 150 years since Jean-Jacques Schloesing and Achille Müntz discovered that the process of nitrification, the oxidation of ammonium to nitrate, is a biological process carried out by microorganisms. In the following 15 years, numerous researchers independently contributed paradigm shifting discoveries that formed the foundation of nitrification and nitrification-related research. One of them was Sergei Winogradsky, whose major accomplishments include the discovery of both lithotrophy (in sulfur-oxidizing bacteria), and chemoautotrophy (in nitrifying bacteria). However, Winogradsky often receives most of the credit for many other foundational nitrification discoveries made by his contemporaries. This accumulation of credit over time is at least in part due to the increased attention Winogradsky enjoys in the scientific literature and textbooks as a “founder of microbiology” and “the founder of microbial ecology”. Here, some light is shed on several other researchers who are often overlooked, but whose work was instrumental to the emerging field of nitrification and to the work of Winogradsky himself. Specifically, the discovery of the biological process of nitrification by Schloesing and Müntz, the isolation of the first nitrifier by Grace and Percy Frankland, and the observation that nitrification is carried out by two distinct groups of microorganisms by Robert Warington are highlighted. Finally, the more recent discoveries of the chemolithoautotrophic ammonia-oxidizing archaea and complete ammonia oxidizers are put into this historical context.